Numerical study of microfluidic emulsion dynamics under the influence of heterogeneous surface wettability. (February 2022) - Chen, Zhe (Ashley); Huang, Fenglei; Tsai, Peichun Amy; Komrakova, Alexandra
Abstract: Surface wettability plays a vital role in various natural phenomena and technical applications, such as coating, printing, membrane technology, microfluidic devices, and porous media flow. We numerically investigate the dynamics and stability of liquid–liquid dispersion flowing in a microfluidic channel with heterogeneous surface wettability, using a conservative phase-field lattice Boltzmann method. First, we validate the implementation of the wetting boundary conditions. We then perform three-dimensional simulations of a single drop motion immersed in another immiscible liquid in a square microchannel with alternating surface wettability: hydrophilic, hydrophobic, and again hydrophilic sections. The viscosity of the dispersed liquid (oil) is ten times higher than that of the continuous one (water), while the two liquids have equal densities. Depending on the drop length and Capillary number, calculated based on the drop velocity and the dynamic viscosity of the continuous phase, four different flow patterns are observed when the drop passes through the hydrophobic section. The distinct flow patterns include passing without any changes in drop shape or dynamics, adhesion of the dispersed liquid to the walls, phase inversion (i.e., water becomes the dispersed phase), and drop breakage. These outcomes are in close agreement with the experimental data. A detailed explanation of the choice of the numerical parameters is presented. The critical aspect of capturing the observed drop behavior is introducing an intervening thin-film of the continuous phase of at least three diffuse interface thicknesses (between the drop and channel walls). Highlights: Emulsion behavior in a heterogeneously coated microchannel is studied numerically. A conservative phase-field lattice Boltzmann method is used. Four flow patterns of emulsion: passing, adhesion, inversion, breaking are observed. Numerical settings leading to physically realistic results are reported. The initial thin film should be 3 times larger than the diffuse interface thickness.